Golgi protein 73: the driver of inflammation in the immune and tumor microenvironment - Feng, Pingping; Hu, Xinyang; Zhou, Sining; Liu, Xianyong; Zeng, Linghui; Liu, Yiming (Frontiers in Immunology, 2025)
Golgi Protein 73 (GP73) is a Golgi-resident protein that is highly expressed in primary tumor tissues. Initially identified as an oncoprotein, GP73 has been shown to promote tumor development, particularly by mediating the transport of proteins related to epithelial-mesenchymal transition (EMT), thus facilitating tumor cell EMT. Though our previous review has summarized the functional roles of GP73 in intracellular signal transduction and its various mechanisms in promoting EMT, recent studies have revealed that GP73 plays a crucial role in regulating the tumor and immune microenvironment. GP73 can modulate intracellular signaling pathways to influence cytokine and chemokine networks, resulting in inflammation caused by viral and bacterial infection or immune diseases, and leading tumor microenvironment deteriorated. Additionally, extracellular GP73 can also regulate signaling pathways of target cells by binding to their cell-surface receptors or entering the acceptor cells, thereby facilitating inflammation or promoting tumor development. In this review, we aim to summarize the findings, providing insights for future investigations on GP73 and its potential as a therapeutic target in ameliorating chronic inflammation in the immune and tumor microenvironment.